PENGARUH RETURN ON ASSETS, SALES GROWTH, KOMITE AUDIT, KOMISARIS INDEPENDEN DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2014-2016) - Endang Sri Wahyuni, 14.05.52.0048; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2018)
The purpose of this research is to examine the influence of return on assets, sales growth, commite audite, independent commissioner and firm size to tax avoidance. The population of this research is all manufactured companies listed in Indonesia Stock Exchange from 2014 to 2016. Samples are obtained through purposive sampling method, in which only 49 of listed manufactured companies in Indonesia Stock Exchange meet the sampling criterias resulting 147 data avaibel are taken as the sampels. The research multiple regression method to test the effect of each variable in influencing tax avoidance. The empirical result indicates that return on asset and commite audite have influence to tax avoidance. However sales growth, independent commissioner and firm size no influence to tax avoidance.Keywords: Tax Avoidance, Return On Assets, Sales Growth, Commite Audite, Independent Commissioner, Firm size